Talking gender and sexuality - McIlvenny, Paul. (Amsterdam ; Philadelphia : John Benjamins, 2002)
This edited volume brings together scholars from psychology, linguistics, sociology and communication science to investigate how performative notions of gender and sexuality can be fruitfully explored with the rich set of tools that have been developed by conversation analysis and discursive psychology for analyzing everyday practical language use, agency and identity in talk. Contributors re-examine the foundations of earlier research on gender in spoken interaction, critically appraise this research to see if and how it 'translates' successfully into the study of sexuality in talk, and promot.
Introduction: Researching talk, gender and sexuality / Paul McIlvenny -- Doing feminist conversation analysis / Celia Kitzinger -- Gender and sexuality in talk-in-interaction: considering conversation analytic perspectives / Elizabeth Stokoe, Janet Smithson -- Critical reflections on performativity and the 'un/doing' of gender and sexuality in talk / Paul McIlvenny -- From performatives to practices / Judith Butler, discursive psychology and the management of heterosexist talk / Susan Speer, Jonathan Potter -- Negotiating gender identities and sexual agency in elderly couples' talk / Liisa Tainio -- Framing gender: incongruous gendered identities in Dar es Salaam adolescents' talk / Sigurd D'hondt -- Repressed on parole: gender categorisation, performativity and the unsaid in talkin' dirty jokes / Andrew Fish -- Figuring gender in teachers' talk about school bullying / Alexa Hepburn -- "I'm still not sure she's a she": textual talk and typed bodies in online interaction / Jenny Sundén.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Conversation analysis; Language and sex; Feminism; Feminism; Analyse de la conversation; Langage et sexualité.; Féminisme.; feminism; REFERENCE; LANGUAGE ARTS & DISCIPLINES -- Vocabulary; Conversation analysis; Feminism; Language and sex; Diskursanalyse; Feminismus; Geschlechterforschung; Geschlechterrolle; Sexualität; Sprache; Geschlechtsunterschied; Identität; Discourse analysis; Sekseverschillen; Feminisme; Diskursanalyse -- Geschlechtsspezifische Sprache -- Kongressbericht; Geschlechtsspezifische Sprache -- Diskursanalyse -- Kongressbericht; Sexualität.; Sprache; Geschlechterforschung; Konversationsanalyse; Geschlechterrolle; Conversation analysis; Language and gender -- Conversation; Conversation analysis; Language and sex; Feminism; Conversation; Ethnométhodologie.; discours oral; sexe (genre); Analisi del discorso; Sesso e linguaggio; Kongress -- Ålborg -- 1999.; Aufsatzsammlung; [Études diverses]